Financial Inclusion as a Pathway to Sustainable Development: Regional Evidence from ASEAN and the Case of Vietnam - Nguyen Tien Khoi; Le Quoc Dinh (Journal of Applied Data Sciences, 2026)
This study investigates the impact of Financial Inclusion (FI) on Sustainable Development (SD) in ASEAN countries over the period 2004–2022, aiming to provide robust regional and country-level empirical evidence using a Bayesian econometric framework. The core idea of the study is that inclusive financial systems serve as a critical transmission channel through which economic, social, and environmental dimensions of sustainable development can be jointly enhanced. The primary objective is to quantify the effect of FI on SD at the ASEAN level and to examine whether this relationship remains consistent when regional evidence is incorporated as prior information for country-level estimation. Using Bayesian regression, the results reveal a strong and positive effect of FI on SD, with an estimated posterior mean coefficient of 15.531 for ASEAN countries and 15.5448 for Vietnam. The posterior probability associated with these coefficients is approximately 1.000 (≈100%), indicating an extremely high level of statistical confidence in the positive FI–SD relationship. Markov Chain Monte Carlo (MCMC) diagnostics confirm convergence and parameter stability across iterations, supporting the reliability of the Bayesian estimates. Robustness checks using Pooled Ordinary Least Squares (POLS) and Feasible Generalized Least Squares (FGLS) yield consistent coefficient signs and magnitudes, further validating the main findings. The results demonstrate that economies with higher levels of financial inclusion tend to achieve significantly better sustainable development performance. The key contribution and novelty of this study lie in its Bayesian regional-to-country estimation strategy, which integrates ASEAN-level evidence as informative priors to strengthen country-specific inference, thereby offering new methodological and policy-relevant insights into the finance–sustainability nexus.